A Pilot Study of Radiation Therapy in Combination With Pembrolizumab in Patients With Metastatic Renal Cell Cancer. (February 2020) - Lin, Jianqing; Song, Andrew J.; Hoffman-Censits, Jean; Leiby, Benjamin E.; Tuluc, Madalina; Shaw, Colette; Harshyne, Larry; Kean, Rhonda; Bar-Ad, Voichita; Den, Robert B.; Hurwitz, Mark D.; Louie, Jennifer; et al.
Abstract : Objectives: There is no study published regarding the benefit of radiation therapy (RT) in combination with immune checkpoint inhibitors (ICIs) for the treatment of metastatic renal cell cancer (mRCC). This report is part of an exploratory study aiming to determine the immunomodulatory activity of RT alone or in combination with pembrolizumab in solid tumors. Materials and Methods: mRCC patients were treated with a combination of RT (8 Gy×1 or 4 Gy×5) followed by pembrolizumab with or without lead-in dose of pembrolizumab. Treatment response was measured based on the modified Response Evaluation Criteria in Solid Tumors criteria. Adverse events were monitored and graded. Pre-RT and post-RT tumor biopsies were obtained to evaluate programmed death-ligand 1 expression. Immune markers from peripheral blood before, during, and after treatment were analyzed using flow cytometry. Results: Twelve mRCC patients who progressed on prior antiangiogenic therapy were enrolled. Half had 2 lines of prior therapy. Two patients (16.7%) had partial responses and were on study for 12.4 and 14.5 months. Three patients had stable disease for a period ranging from 4.2 to 10.4 months, whereas 7 patients had progressive disease. Median progression-free survival was 8.6 months and median overall survival was 32.3 months. Three patients had grade ≥3 events (hyperglycemia, thrombocytopenia, transaminitis). Biopsied tissue programmed death-ligand 1 expression and tumor-infiltrating lymphocytes were numerically higher in responders comparing to nonresponders (Modified Proportion Score 45% vs. 30.45%; tumor-infiltrating lymphocytes odds ratio 4.92). Conclusion: Combining RT with pembrolizumab in pretreated mRCC is well-tolerated and appears to have comparable efficacy with single-agent nivolumab.